Satellite altimetry detection of ice-shelf-influenced fast ice - G. M. Brett; D. Price; W. Rack; P. J. Langhorne (The Cryosphere, 2021)
The outflow of supercooled Ice Shelf Water from the conjoined Ross and McMurdo ice shelf cavity augments fast ice thickness and forms a thick sub-ice platelet layer in McMurdo Sound. Here, we investigate whether the CryoSat-2 satellite radar altimeter can consistently detect the higher freeboard caused by the thicker fast ice combined with the buoyant forcing of a sub-ice platelet layer beneath. Freeboards obtained from CryoSat-2 were compared with 4 years of drill-hole-measured sea ice freeboard, snow depth, and sea ice and sub-ice platelet layer thicknesses in McMurdo Sound in November 2011, 2013, 2017 and 2018. The spatial distribution of higher CryoSat-2 freeboard concurred with the distributions of thicker ice-shelf-influenced fast ice and the sub-ice platelet layer. The mean CryoSat-2 freeboard was 0.07–0.09 m higher over the main path of supercooled Ice Shelf Water outflow, in the centre of the sound, relative to the west and east. In this central region, the mean CryoSat-2-derived ice thickness was 35 % larger than the mean drill-hole-measured fast ice thickness. We attribute this overestimate in satellite-altimeter-obtained ice thickness to the additional buoyant forcing of the sub-ice platelet layer which had a mean thickness of 3.90 m in the centre. We demonstrate the capability of CryoSat-2 to detect higher Ice Shelf Water-influenced fast ice freeboard in McMurdo Sound. Further development of this method could provide a tool to identify regions of ice-shelf-influenced fast ice elsewhere on the Antarctic coastline with adequate information on the snow layer.